Application of Expert System Identification of Horticultural Plant Diseases with Certainty Factor and Forward Chaining for Smart Village Concept Development - Damar Wicaksono; Imam Adi Nata (Jurusan Informatika, 2023)
Purpose: This research was conducted to help identify diseases early and provide suggestions for recommendation systems for these plants in general that are beneficial for farmers.Design/methodology/approach: This research goes through several stages, namely planning , analysis, design, and implementation.Findings/result: CLIPS-based Horticultural Plant Disease Identification Expert SystemOriginality/value/state of the art: In the process of diagnosing plant diseases, it requires the accuracy and thoroughness of an expert or experts on symptoms that indicate a disease because of the similarity of these symptoms. Misdiagnosis of existing symptoms causes differences in the results of the diagnosis with the actual disease suffered by the plant. Along with the development of technology, a system was devised that would help report early identification of diseases and provide suggestions for recommendation systems for these plants in general that are beneficial to farmers.